Clinical pharmacists: The major support to Indian healthcare system in near future - Prasanna R Deshpande; Raghuram Vantipalli; C H Chaitanya Lakshmi; E Jagadeswara Rao; Bishnu Regmi; Abdul Ahad; P Sharmila Nirojini (Wolters Kluwer Medknow Publications, 2015)
Pharmacy practice is still in the initial stages of development in India, but launching of Doctor of Pharmacy (PharmD) study program has brought serious discussions about clinical pharmacy in the country. As the profession is in budding stage in the country, the patients, physicians, nurses, other healthcare providers, recruiters in pharmaceutical industries, prospective students, and their parents have numerous questions about this profession and study course. The objective of this article is to create awareness about clinical pharmacy services (CPS) and to introduce the role of clinical pharmacists (CPs). After reading this article, one will know about the usefulness of CPs in the Indian healthcare system against the current flaws in the system. The article describes the role of CPs in the hospitals, in research, in pharmaceutical/contract research companies, in community service and it also tells about the related myths and facts. Prospective job opportunities for CPs, present challenges and the possible solutions are elaborated as well. In conclusion, CPs are going to be the major support to the Indian healthcare system in near future; the reasons being (1) CPS are beneficial in many ways to improve healthcare; CPS have already proved their importance in western countries (2) India was never officially and efficiently exposed to CPS; so launching of CPS shall revolutionize the country's healthcare scenario.